2020
DOI: 10.1016/j.cyto.2020.155190
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine prediction of mortality in COVID19 patients

Abstract: Coronavirus disease 2019 (COVID19) is a life-threatening infection with uncertain progression and outcome. Assessing the severity of the disease for worsening patients is of importance in making decisions related to supportive mechanical ventilation and aggressive treatments. This was a prospective, non-randomized study that included hospitalized patients diagnosed with COVID19. Pro-inflammatory cytokines were assessed during hospitalization, and we calculated a prediction paradigm for 30-day mortality based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 17 publications
(17 reference statements)
4
70
0
Order By: Relevance
“…There is a substantial body of evidence linking the IL-6 concentration to the severity of disease and unfavorable outcome of Covid-19 [11,12,13,14,15,16,18,19,20]. However, to our knowledge, this study is the rst study which evaluated the ability of IL-6 to predict the need for supplementary oxygen administration as a surrogate marker of severe Covid-19 requiring hospital admission in the population of high risk elderly patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is a substantial body of evidence linking the IL-6 concentration to the severity of disease and unfavorable outcome of Covid-19 [11,12,13,14,15,16,18,19,20]. However, to our knowledge, this study is the rst study which evaluated the ability of IL-6 to predict the need for supplementary oxygen administration as a surrogate marker of severe Covid-19 requiring hospital admission in the population of high risk elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…The theory that IL-1β have an important role in the pathogenesis of Covid-19 is widely accepted [30]. However, recent study by Mandel et al found that baseline concentration of IL-1β is not signi cantly higher in nonsurvivors [20]. Giamarellos-Bourboulis et al concluded that immune dysregulation in severe Covid-19 is directly driven by IL-6, not IL-1β upregulation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for extravascular fluid leakage into the lungs in COVID-19 is secretion of proinflammatory cytokines such as TNF and IL-6 during the cytokine storm (Fig 1, A). 7 We favor a third hypothesis, where excessive and prolonged secretion of type I and type III IFNs in the airways contributes to loss of lung epithelial barrier function during COVID-19 and other RNA virus infections (Fig 1, A). 8,9 To test whether entry of SARS-CoV-2 through ACE-2 is sufficient to induce type III IFNs without need for viral replication, we engineered a replication-deficient SARS-CoV-2 spike-HIV-luc pseudotype virus.…”
mentioning
confidence: 87%
“…The normal range for IL-1beta is 0.10pg/mL, and it could exceed 0.67pg/ml during disease [103].The normal range for TNF alpha is 0.0-8.1 pg/mL, and it could exceed 35pg/mL during disease [99,104]. Cytokine cut-offs are difficult to establish and may vary depending on several factors such as population genetics, pleiotropic nature, and health status of patient.…”
Section: Cytokinesmentioning
confidence: 99%